Effects Of Sensory Marketing On Customer’s Future Behavioral Intentions In Casual Dining Restaurant - Sulaiman, Suria (2020)
The trend of eating out in Malaysia has led to the growth of this industry supported by the other emerging trends such as higher income and higher population especially in urban area. In relation to the above matter, several theories and concepts been tested and applied to the market to compete in the industry and retain the customers including the concept of sensory marketing. However, the use of sensory marketing still suffers of a lack of awareness from the marketers in the industry. This leads to the difficulty of setting up proper sensorial techniques in the restaurant industry. The purpose of this study is to examine the effects of sensory marketing constructs- dinescape, foodscape and logoscape towards future behavioral intentions of the customer directly and through emotions and perceived value in casual dining restaurant. The underpinning theory used is the Stimulus-Organism- response theory. Descriptive analysis and structural equation modeling were used to test all the hypotheses of the study. The result of 234 respondents show that service staff, freshness, taste, credit card logo and halal logo have effects towards future behavioral intentions of the customer. The findings also indicated that perceived value mediates the relationship between service staff, freshness, taste and credit card logo, grading logo and wi-fi logo and future behavioral intentions. Emotion on the other hand, did not have any effects on the constructs as a mediator. This study makes both theoretical and practical contributions, especially revealing the trends and preferences of customer in Malaysia towards the use of Sensory Marketing for a restaurant.